How Executive Directors' Remuneration is Determined in Two FTSE 350 Companies: Results of an Exploratory Study - Bender, Ruth (Cranfield University, 2002)
This paper sets out the results of interview-based research into the way in which executive directors’ remuneration is set in two UK utilities. Although the subject of executive directors’ remuneration has been widely researched, little work has addressed the question ‘how is the directors’ remuneration determined?’. This study addresses that research gap through direct and in-depth questioning of key people involved in the remuneration-setting process. Research was carried out at two UK utilities, both listed in the FTSE 350. In each company, interviews were conducted individually with the key executives and non executives involved in the remuneration-setting process, and with the compensation consultants who acted as their advisors, to determine the processes undertaken and the factors affecting their decisions. The interviews were semi structured, in order to enable open discussion and ensure a wide-ranging discussion of the protagonists’ actions and reasoning. The findings of the research project reflected both economic and social-psychological theories adopted in the executive remuneration literature. The interviews showed that the level and structure of remuneration were clearly influenced by ‘the market’, although issues were surfaced about the problems of determining a suitable comparator market. Institutional theory influences were identified in the level and structure of the pay, and the way trends in practices influenced the protagonists. Furthermore, the way in which the companies’ policies were tailored to their corporate strategies was consistent with c